Juridical Analysis of the Existence of Digital Nomads from an Indonesian Positive Legal Perspective - Ketut Lanang Sukawati P. Perbawa; Putu Lantika Oka Permadhi (International Journal of Social Science and Business, 2023)
The Covid-19 pandemic has greatly affected all industrial sectors, especially tourism. One effort to increase tourism development again after the COVID-19 pandemic is through the development of information technology, one of which is digital tourism. This research aims to analyze the existence of digital nomads in Indonesia from a positive legal perspective. The type of research used is normative law, which is research based on secondary data. This research uses an approach to legislation (the statute approach) and an approach to analyzing legal concepts (the analytical and conceptual approach), which is then studied using a legal interpretation of argumentative descriptions based on principles, legal concepts, and theories relevant to the research problem. The research results show that the effect of digital tourism is the emergence of digital nomads who provide a work style and culture while on holiday for both domestic and foreign tourists. However, the problem is from the perspective of positive Indonesian Law, where there are no clear regulations regarding digital tourism in Indonesia, so a juridical analysis must be carried out regarding the existence of digital nomads.